Synergistic promoting effect of ball milling and KF–alumina support as a green tool for solvent-free synthesis of 2-arylidene-benzothiazinones. (1st November 2016) - Sharifi, Ali; Ansari, Mohammad; Darabi, Hossein Reza; Abaee, M. Saeed
ABSTRACT: A solvent-free procedure is developed for the reaction of benzothiazinones with benzaldehyde derivatives, where the solid KF–Al2 O3 support and ball milling synergistically leads to a green and efficient synthesis of several 2-arylidene-benzothiazinones. Therefore, a cooperative effect of the solid support and ball milling leads to excellent yields of the target dienes, while the catalyst can be recycled for subsequent reactions without significant loss of its activity. GRAPHICAL ABSTRACT: